I soffitti lignei del palazzo di Cosimo dei Medici a Milano e alcuni esempi di diffusione dei lacunari all’antica in Lombardia - Gritti, Jessica (Opus Incertum, 2018)
The remains of the house owned by Cosimo Medici in Milan – a building given by Francesco Sforza to the Medicis in 1455 and reconstructed to become the office of the Medici Bank in the city – does not permit to undestand the rich presence of wooden ceilings. The description by Filarete and some 19th century sources, before the complete transformation of the house, show us an image of the coffered ceiling of the main room on the first floor, and the carpentry used for arcades and loggias in the courtyard. The decoration of the wooden ceiling of the main room seems to have been very well known in Milan during the second half of the 15th century, which explains why Galeazzo Maria Sforza wanted the wooden ceiling of his own chapel in the church of St. Celso in 1473 with coffers similar to those of two important models, the Medici bank and the chapel of the Santissima Annunziata in Florence. The essay illustrates the sources concerning the wooden ceilings of the Medici bank and some examples of their diffusion in Lombardy during the second half of the 15th century.